1992
DOI: 10.1177/001872089203400506
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Judgments with Monoscopic and Stereoscopic Presentation of Perspective Displays

Abstract: Spatial judgments with monoscopic and stereoscopic presentation of perspective displays were investigated in the present study. The stimulus configuration emulated a visual scene consisting of a volume of airspace above a ground reference plane. Two target symbols were situated at various positions in the space, and observers were instructed to identify the relative depth or altitude of the two symbols. Three viewing orientations (15, 45, or 90 deg elevation angle) were implemented in the perspective projectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(30 citation statements)
references
References 19 publications
2
27
1
Order By: Relevance
“…These augmentations have an associated cost. Yeh and Silverstein (1992) have labelled these augmentations "crutches" because they clutter the display with unnatural additions. For example, drop-shadows essentially doubles the number of air track symbols in the display.…”
Section: Introductionmentioning
confidence: 99%
“…These augmentations have an associated cost. Yeh and Silverstein (1992) have labelled these augmentations "crutches" because they clutter the display with unnatural additions. For example, drop-shadows essentially doubles the number of air track symbols in the display.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yeh and Silverstein (1992) found that the addition of stereopsis led to faster and more-accurate spatial judgments than a perspective display alone. Furthermore, Kim, Ellis, Tyler, Hannaford, and Stark (1987) examined the effect of stereopsis and perspective cues on subjects' ability to manually track an object.…”
Section: Introductionmentioning
confidence: 99%
“…Without the egocentric information you cannot judge whether an object lies in front, on, or behind the Vieth-Mu¨ller circle [48][49][50].…”
Section: Physiology Of Three-dimensional Visionmentioning
confidence: 99%